POLITIK AKOMODATIF DALAM MASYARAKAT MULTI AGAMA - Katon Galih Setyawan; Kusnul Khotimah (The Journal of Society and Media, 2019)
Tapered political and economic interests have become a religious problem that is prevalent in Indonesia. Even opposition to the religious background in East Java is very high and the East Java community is ranked second as an intolerant society in Indonesia. But not so in the multi-religious Resapombo Village they lived in harmony and side by side without any open conflict among the community. Therefore in this study the focus of the study was based on how the role of the BPD and LPMD was interpreted by the Resapombo Village community to play a role in managing inter-religious harmony. This study uses the perspective of Blumer symbolic interaction, namely social interaction can be understood through the meaning interpreted by the actor. This study uses qualitative research methods with a phenomenological approach. In fostering harmony between religious communities a long social process takes place and becomes entrenched nowadays and is interpreted or interpreted by the perpetrators themselves and it can be claimed as their own local wisdom. The social process can take the form of several mutual cooperation activities and consensus agreements. with the existence of official village institutions in the form of BPD and LPMD which are accommodative places to accommodate all political interests at the village level.